Effects of Process Variations in a HCMOS IC using a Monte Carlo SPICE Simulation - Widianto, Widianto; Syafaah, Lailis; Nurhadi, Nurhadi (Universitas Muhammadiyah Malang, 2018)
In this paper, effects of process variations in a HCMOS (High-Speed Complementary Metal Oxide Semiconductor) IC (Integrated Circuit) are examined using a Monte Carlo SPICE (Simulation Program with Integrated Circuit Emphasis) simulation. The variations of the IC are L and VTO variations. An evaluation method is used to evaluate the effects of the variations by modeling it using a normal (Gaussian) distribution. The simulation results show that the IC may be detected as a defective IC caused by the variations based on large supply currents flow to it.Â